2012
DOI: 10.1515/epoly.2012.12.1.722
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical applications of electrically conductive polymeric systems

Abstract: Properties of the electrically conductive polymers (ECPs) enable introduction of several novel applications in various fields, among others, as biomedical materials. Their use as scaffolds for tissue engineering and recovery of damaged neural tissues is especially advantageous. They may also be used for the electrically induced drug release and delivery, and as very sensitive biosensors for clinical applications. Another use is the detection and precision of the biologically important chemical materials. They … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 96 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…This new generation of "smart" biomaterials have been investigated for applications in biosensors; coatings on conventional electrodes used in neural sensing and stimulation; electrically induced drug release and delivery systems; modulators of activities of nerve, cardiac, skeletal muscle, and bone cells; and in emerging technologies such as tissue engineering. 13 The most widely investigated conducting polymers for biomedical applications include polypyrrole, polyaniline, polythiophene and its derivatives such as poly(3,4-ethylenedioxythiophene). [14][15][16][17] Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This new generation of "smart" biomaterials have been investigated for applications in biosensors; coatings on conventional electrodes used in neural sensing and stimulation; electrically induced drug release and delivery systems; modulators of activities of nerve, cardiac, skeletal muscle, and bone cells; and in emerging technologies such as tissue engineering. 13 The most widely investigated conducting polymers for biomedical applications include polypyrrole, polyaniline, polythiophene and its derivatives such as poly(3,4-ethylenedioxythiophene). [14][15][16][17] Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, as ECPs have also extended to biotechnological, bioengineering and biomedical fields, [36][37][38][39] special attention has been paid to tailor desirable properties (i.e. electrical, chemical and physical properties) to better suit the nature of the specific bioapplication.…”
Section: Electroactive Conducting Polymersmentioning
confidence: 99%
“…[36][37][38][39][40] In particular, for tissue engineering applications, ECPs show interesting advantages but also some limitations (i.e. hydrophobicity, the lack of mechanical integrity and the absence of biodegradability).…”
Section: Electroactive Conducting Polymersmentioning
confidence: 99%
“…Electrical signals are critical physiological stimuli factors that control the adhesion and differentiation of certain cell types (for example, nerve, cardiac, and bone). To retain cellular bioactivity and enhance overall properties of scaffold, CNMs have lately emerged as promising candidates in producing scaffolds to better mimic the natural ECM and to efficiently replace defective tissues . For instance, Hsiao et al prepared aligned PANI/poly(lactic acid‐ co ‐glycolic acid) (PLGA) conductive nanofibrous mesh via electrospinning technique.…”
Section: Cnms Used In Tissue Engineeringmentioning
confidence: 99%
“…To retain cellular bioactivity and enhance overall properties of scaffold, CNMs have lately emerged as promising candidates in producing scaffolds to better mimic the natural ECM and to efficiently replace defective tissues. 61 For instance, Hsiao et al prepared aligned PANI/poly(lactic acid-co-glycolic acid) (PLGA) conductive nanofibrous mesh via electrospinning technique. Their result demonstrated that the nanocomposite promoted cardiomyocyte adhesion due to the positive charges they transformed, and the fluorescence micrographs were shown in Figure 2.…”
Section: Cnms Used In Tissue Engineeringmentioning
confidence: 99%